Continual improvement (CI) lean culture continuous quality and cost saving in Malaysia manufacturing & engineering (M&E) companies - Rasidah Abu,; Nurul Hayati Abdul Halim,; Azianti Ismail,; Falah Abu,; Sha’ri Mohd. Yusof,; Noor Azlina Mohd. Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Lean sustainability is often perceived to only be possible to be maintained via small group application of lean culture that carry out improvement activities. The purpose of this case study is thus to examine the success factors of inculcating lean culture framework by lean practitioners in Malaysian Manufacturing and Engineering (ME) companies that faced inconsistencies in implementing and sustaining lean. The impact of lean culture framework practiced by Small Group Improvement Activities (SGIA) was analysed via productivity improvement methodologies comprises of semi-structured interviews and analysis of 633 Small Group Improvement Activities (SGIA) project reports in establishing a final lean culture framework that can contribute to the longevity of a lean company. The improved lean culture framework that had been extended to other strategic business units (SBU) in ME companies are found to be the positive factor contributing to the sustainability of lean culture and achieving tangible and intangible benefits via small group improvement activities, enhancement standard which include companies’ policy, as well as providing a guideline in problem solving methodology. The findings revealed that enhancement of inculcating lean framework is crucially in need especially in expanding the initiatives across ME companies via a systematic and standardised problem-solving methodology. This study intends to aid organisations, practitioners, academicians, and respective industries in benchmarking the best practises and at the same time further reduce the gap and continually improve the lean culture framework in other compass industries.